Pemanfaatan Gula Khas Baduy untuk Produk Olahan Bolu Kukus: Upaya Pemberdayaan Ekonomi Berbasis Komunitas Baduy Mualaf - Afiyah, Anisa Nur; Safitri, Lili Dwi; Batavia, Meisya Andin; Ainina, Ananda Nur; Putri, Fitria Dwi Risna; Safitri, Safitri; Romansyah, Nano; Zunaidi, Arif; Ignacia, Jessica Emery (Fakultas Ekonomi dan Bisnis Islam, IAIN Kediri, 2025)
This community service aims to improve the economic skills of Baduy Mualaf residents in Kampung Lembah Barokah Ciboleger (LBC), Bojong Menteng Village, Banten, through training in making brown sugar steamed cake made from Baduy sugar. The activity was carried out on January 28, 2025 and was attended by 18 housewives. This training uses the Participatory Action Research (PAR) and Asset-Based Community Development (ABCD) approaches which emphasize active community participation and the utilization of local potential. The training materials include techniques for making steamed cake, packaging, and simple marketing strategies. The results of the activity showed that the majority of participants were able to practice the techniques taught and showed interest in making it a home business. This training not only improves technical skills but also builds an entrepreneurial spirit. In conclusion, this training is effective in encouraging community-based economic empowerment and can be a model for developing micro-enterprises in similar areas.